HUBUNGAN CARA BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA PRODI PKK KONSENTRASI TATA BOGA JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNP - ROHATI, RIDA; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2014)
This study aims to determine the relationship between learning and the learning achievement of students Prodi PKK concentration Catering Family Welfare Department, Faculty of, State University of Padang. This type of research is correlational. The selection of informants in this study using proportional random sampling technique with a sample of 91 people with research subjects Catering students from the incoming 2008 s/d 2011. Data collection techniques using a Likert scale questionnaire models. The results showed that there is a significant positive relationship between learning and the learning achievement of students Prodi PKK concentration Catering Family Welfare Department, Faculty of Engineering UNP. And suggestions for student learning so that more families than ever due to enhanced learning achievement is one indicator that shows the success in the learning process. Â  Keywords: relationships, learning, learning achievement